PENGELOLAAN HUTAN ADAT DENGAN PRINSIP KEARIFAN LOKAL (STUDY DI HUTAN ADAT RIAM BATU, KECAMATAN TEMPUNAK, KABUPATEN SINTANG, PROVINSI KALIMANTAN BARAT) - Purba, Daud Prihatinro; Mardawani, Mardawani (JURNAL PEKAN : Jurnal Pendidikan Kewarganegaraan, 2023)
The granting of forest management rights through customary forests is a form of state recognition for indigenous peoples in Indonesia to manage and protect their forests with the principles of local wisdom. The granting of these rights is carried out through an agrarian reform mechanism, one of which is the social forestry program launched in 2015 by the Ministry of Environment and Forestry. This research was conducted to find out how the Seberuang Dayak indigenous people of Riam Batu Village manage and protect the forest with the principles of local wisdom that have long been passed down from generation to generation. Data collection was carried out through interviews, discussions (FGD), and field observations. Meanwhile, data analysis was done descriptively. From this study, it shows that the Dayak Seberuang indigenous people of Riam Batu Village have a close relationship with the forest, so the authors obtain the following results: (1). In managing customary forests, the Riam Batu Customary Law Community is guided by customary rules that have been in force for generations, namely bodily customs and base customs. (2). With the customary forest, it provides benefits for the life of the people of Riam Batu Village.Keywords: Customary Forest, Indigenous Peoples (MHA), Local Wisdom, Social Forestry.